2019
DOI: 10.1177/2055207619890473
|View full text |Cite
|
Sign up to set email alerts
|

Morbid curiosity? Discussion of the disposal of amputated limbs on online question and answer sites

Abstract: Amputation is a growing health issue with implications for the corporeal form and sense of bodily identity. Disposal of the removed limb (the amputate) has historically been suggested to impact on patient adaptation to amputation, although understandings of limb disposal are scarce within existing research. The growth of online question and answer sites has created opportunities for social actors to post and respond to a vast array of topic areas, including those that are seen as morbid or taboo. This paper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The return of the amputated limb may be important to the patient for cultural, social, religious, or spiritual reasons 1 . Patients undergoing limb amputation can experience grief equivalent to the loss of a spouse as well as changes in their quality of life, mental health, 4 body image, and sense of self 4,5 . Some cultures and religions, including Catholicism, Judaism, and Islam, have specific requirements for the burial of bodies and body parts 6,7 .…”
Section: Releasing Amputated Limbsmentioning
confidence: 99%
“…The return of the amputated limb may be important to the patient for cultural, social, religious, or spiritual reasons 1 . Patients undergoing limb amputation can experience grief equivalent to the loss of a spouse as well as changes in their quality of life, mental health, 4 body image, and sense of self 4,5 . Some cultures and religions, including Catholicism, Judaism, and Islam, have specific requirements for the burial of bodies and body parts 6,7 .…”
Section: Releasing Amputated Limbsmentioning
confidence: 99%
“…Thus, for some patients, the ownership question remains the central factor for why they seek to influence the disposal of their limb, and indeed our previous research into lay perspectives around limb disposal primarily identified that people believe amputated limbs should 'belong' to those from who they originated (Hanna, 2019b). However, the proprietorial aspect only goes so far within the justification of why patients want their limb returned to them, or for them to influence its disposal.…”
Section: Why Is Disposal An Issue?mentioning
confidence: 99%
“…They also offer less possibility for the memorialisation of the lost limb – shared sites, being as they are a collective entity, and in the case of the site at Sheffield the internment of the limbs into the grave is mediated via clinical and state services, namely the mortuary and council staff within the city. Other options for how ‘estranged limbs’ are disposed of after amputation do exist, although often narrated through more abject or grotesque discourses (Hanna, 2019b). This currently serves to further position ‘disposal’ as unusual, enforcing normative positions, whereby ‘our bodies in parts’ (Sobchack, 2010: 55) are seen as particularly challenging of our ideals of bodily integrity and disposal practices relating more readily to contexts of corporeal wholeness.…”
Section: Patient Choice In Disposalmentioning
confidence: 99%
See 2 more Smart Citations